Polypharmacology of dopamine D1-like receptor antagonists - Nikolić Katarina; Filipić Slavica; Agbaba Danica (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2015)
Drug discovery based on development of selective ligands for a specific target intended to modulate its activity and revert pathophysiological process is now recognized as too simplistic to design effective agent for complex multifactorial diseases, characterized by diverse physiological dysfunctions caused by deregulations of complex networks of proteins. Major challenge in modern drug discovery is to rationally design multitarget drugs able to specifically modulate only a group of desired targets while minimizing interactions with off-targets. Multifactorial cerebral mechanisms implicated in mental (psychiatrics) and neurodegenerative diseases and interactions of the neurotransmitter systems are two main reasons for applying polypharmacology ('multi-target') strategy in drug discovery for these complex brain diseases. In this paper we review polypharmacological profile and potential therapeutic application of dopamine D1-like receptor antagonists.